A Two-Stage Stochastic Dynamic Economic Dispatch Model Considering Wind Uncertainty - Liu, Yang; Nair, Nirmal-Kumar C. (IEEE transactions on sustainable energy, 2016)
This paper proposes a two-stage stochastic dynamic economic dispatch model aiming at better managing system variability and uncertainty influenced by wind generation. Stochastic decomposition algorithm is proposed to solve the model in order to facilitate real-time application. The proposed method is tested on PJM-5 and RTS-24 systems and the results verify that the model inherits advantages from conventional dynamic economic dispatch, which is able to make out of merit order dispatch instructions for future benefits. Furthermore, the proposed model can correct false generator pre-ramp instructions due to forecast error and evaluate potential nodal wise reserve requirement therefore improving reserve deliverability. For computational efficiency assessment, stochastic decomposition is compared with sample average approximation. A modified IEEE-118 bus case study is shown.